DIAGNÓSTICO DE FALHAS INCIPIENTES EM TRANSFORMADORES DE POTÊNCIA UTILIZANDO A TEORIA DA EXTENSÃO - Lima, Shigeaki Leite de (2008)
Power transformers play an important role in the power energy supply, demanding the continuous monitoring of process that could lead to operation faults, specifically in the equipment electric insulation. Methods considered in the standards IEC, IEEE and NBR7274 for dissolved gas analysis (DGA) do not provide good levels of accuracy, because there are scenarios with oil samples that lead to contradictory evaluations. The extension theory is a method based on the idea that contradiction can be transformed into compatible problems. In this work, this theory is applied for solving incompatibilities found in the application of the standard NBR7274 for incipient detection faults (the modified Roger s Method). In order to validate the approach, several test cases from recent literature have been implemented and included. The approach has shown good comparative performance in the fault identification process.